Practicality and Effectiveness of the COMESC Learning Model in Fostering Statistical Thinking Skills - Nio, Tan Hian; Suyitno, Hardi; Kartono, Kartono; Mariani, Scolastika (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
The COMESc learning model is a specialized instructional approach developed through research and development to address university students’ weaknesses in statistical thinking. These weaknesses include challenges in problem identification, hypothesis formulation, selection of appropriate statistical methods, interpretation of statistical relationships, application of significance testing, execution of calculations, comparison of sample and critical values, decision-making, and result interpretation. This study aimed to evaluate the practicality and effectiveness of the COMESc model in improving students’ statistical thinking skills. A limited field trial was conducted with 27 participants over 10 class sessions. Qualitative data were collected through open-ended questionnaires and in-depth interviews, while quantitative data were obtained from closed-ended questionnaires and tests. Results indicated that the COMESc model is highly practical (95.65%) and effective, with 100% of participants achieving a minimum average test score of 73. The model also improved learning outcomes, enhanced performance, and stimulated active learning dynamics. Its strengths lie in ease of implementation, structured problem-solving syntax, and capacity to foster deeper statistical reasoning, while its main limitation is the need for instructor patience during initial implementation.